Strategi Bersaing PT. Perusahaan Gas Negara, Tbk. Area Karawang Guna Meningkatkan Pelanggan - Fauzi, Ahmad Bilal; Nurkhaerani, Fatma (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2024)
The increase in gas use for the household sector in Java Island will continue to increase due to high natural gas market competition, growing electricity demand, rising oil prices, attention to the environment, and growing gas demand. This natural gas provider is faced with the main challenge of having to provide adequate supply to meet the increasing demand for natural gas. In the service sector, companies need a good strategy in order to carry out operational activities with higher efficiency and effectiveness. From these problems, the purpose of this study is to analyze the right business strategy to be marketed to customers. The method used in this study is qualitative descriptive analysis by taking data through interviewing resource persons and making direct observations. Therefore, the results of this study that the strategy obtained from the SWOT analysis is product quality and the number of technician workforce and the alternative strategy is to maintain the company's brand reputation by maintaining the existing market and trying to expand the market to dominate a larger market share. Thus, this research can provide the right strategic plan or alternative for the company.